Nationwide Outcomes of Heart Transplantation for Postpartum Cardiomyopathy - Ilias P. Doulamis; Aspasia Tzani; Ahmet Kilic; Toshiki Kuno; Alexandros Briasoulis (Reviews in Cardiovascular Medicine)
Background: Postpartum cardiomyopathy is defined as an incident of acute heart failure in the postpartum period in the absence of any other cause. Up to 10% of postpartum cardiomyopathy may need to undergo heart transplantation later in life. This study aimed to provide a present-day perspective on all-cause mortality and transplant-related complications after heart transplantation for postpartum cardiomyopathy. Methods: A retrospective analysis of the United Network for Organ Sharing (UNOS) registry was performed for adult patients undergoing heart transplants (01/2001–01/2023) for postpartum cardiomyopathy. Results: A total of 677 patients were identified, with a mean age of 35 years. The mean body mass index (BMI) was 27.2 kg/m2; the most common comorbidity was type 2 diabetes (T2D) (n = 589; 87%). Older age was associated with lower overall mortality (hazard ratio (HR): 0.97; 95% CI: 0.95, 0.98; p < 0.01), while diabetes (HR: 1.01; 95% CI: 1.01, 1.01; p < 0.01), dialysis (HR: 1.01; 95% CI: 1.01, 1.01; p < 0.01), days on Status 1 on the UNOS registry (HR: 1.06; 95% CI: 1.03, 10.9; p < 0.01), creatinine (HR: 1.29; 95% CI: 1.02, 1.64; p = 0.034), and length of stay (HR: 1.01; 95% CI: 1.01, 1.02; p = 0.02) were associated with a higher risk of overall mortality. Moreover, 30-day mortality was 2.8%, and 1-year mortality was 11.1%. The era effect was prominent in cases of 1-year mortality (odds ratio (OR): 0.95; 95% CI: 0.91, 0.99, p = 0.006). Conclusions: Our results suggest that younger age, diabetes, pretransplant dialysis, days on Status 1, and creatinine are associated with higher mortality, while an era effect was observed for 1-year mortality after heart transplantation (HTx) in patients with postpartum cardiomyopathy.